Answer
The derivatives of the functions are:
1. **(a)** \( f'(x) = (3x + 2)(9x + 2) \)
2. **(b)** \( f'(x) = (x - 3)(3x - 1) \)
3. **(c)** \( f'(x) = (4x + 1)^3 (29 - 60x) \)
4. **(d)** \( f'(x) = 4(x + 2)(x^2 + x + 1) \)
Solution
Certainly! Let's differentiate each of the given functions with respect to \( x \). We'll use differentiation rules such as the **Product Rule** and the **Chain Rule** where applicable.
### Problem 1(a):
**Differentiate** \( f(x) = x(3x + 2)^2 \) **with respect to** \( x \).
**Solution:**
We'll use the **Product Rule**, which states that if \( f(x) = u(x) \cdot v(x) \), then
\[
f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x)
\]
Let:
\[
u(x) = x \quad \text{and} \quad v(x) = (3x + 2)^2
\]
First, find \( u'(x) \) and \( v'(x) \):
1. **Differentiate \( u(x) = x \):**
\[
u'(x) = 1
\]
2. **Differentiate \( v(x) = (3x + 2)^2 \) using the **Chain Rule**:
\[
v'(x) = 2(3x + 2) \cdot \frac{d}{dx}(3x + 2) = 2(3x + 2) \cdot 3 = 6(3x + 2)
\]
Now, apply the Product Rule:
\[
f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x) = 1 \cdot (3x + 2)^2 + x \cdot 6(3x + 2)
\]
Simplify the expression:
\[
f'(x) = (3x + 2)^2 + 6x(3x + 2)
\]
\[
f'(x) = (3x + 2)\left[(3x + 2) + 6x\right] = (3x + 2)(9x + 2)
\]
**Final Answer:**
\[
f'(x) = (3x + 2)(9x + 2)
\]
---
### Problem 1(b):
**Differentiate** \( f(x) = (x + 1)(x - 3)^2 \) **with respect to** \( x \).
**Solution:**
Again, we'll use the **Product Rule**.
Let:
\[
u(x) = x + 1 \quad \text{and} \quad v(x) = (x - 3)^2
\]
First, find \( u'(x) \) and \( v'(x) \):
1. **Differentiate \( u(x) = x + 1 \):**
\[
u'(x) = 1
\]
2. **Differentiate \( v(x) = (x - 3)^2 \) using the **Chain Rule**:
\[
v'(x) = 2(x - 3) \cdot \frac{d}{dx}(x - 3) = 2(x - 3) \cdot 1 = 2(x - 3)
\]
Apply the Product Rule:
\[
f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x) = 1 \cdot (x - 3)^2 + (x + 1) \cdot 2(x - 3)
\]
Factor out \( (x - 3) \):
\[
f'(x) = (x - 3)\left[(x - 3) + 2(x + 1)\right]
\]
\[
f'(x) = (x - 3)(x - 3 + 2x + 2) = (x - 3)(3x - 1)
\]
**Final Answer:**
\[
f'(x) = (x - 3)(3x - 1)
\]
---
### Problem 1(c):
**Differentiate** \( f(x) = (2 - 3x)(4x + 1)^4 \) **with respect to** \( x \).
**Solution:**
We'll employ the **Product Rule** once more.
Let:
\[
u(x) = 2 - 3x \quad \text{and} \quad v(x) = (4x + 1)^4
\]
First, find \( u'(x) \) and \( v'(x) \):
1. **Differentiate \( u(x) = 2 - 3x \):**
\[
u'(x) = -3
\]
2. **Differentiate \( v(x) = (4x + 1)^4 \) using the **Chain Rule**:
\[
v'(x) = 4(4x + 1)^3 \cdot \frac{d}{dx}(4x + 1) = 4(4x + 1)^3 \cdot 4 = 16(4x + 1)^3
\]
Apply the Product Rule:
\[
f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x) = (-3)(4x + 1)^4 + (2 - 3x) \cdot 16(4x + 1)^3
\]
Factor out \( (4x + 1)^3 \):
\[
f'(x) = (4x + 1)^3 \left[ -3(4x + 1) + 16(2 - 3x) \right]
\]
\[
= (4x + 1)^3 \left[ -12x - 3 + 32 - 48x \right]
\]
\[
= (4x + 1)^3 (-60x + 29)
\]
**Final Answer:**
\[
f'(x) = (4x + 1)^3 (29 - 60x)
\]
---
### Problem 1(d):
**Differentiate** \( f(x) = (2 + x)^2 (x^2 + 2) \) **with respect to** \( x \).
**Solution:**
We'll use the **Product Rule**.
Let:
\[
u(x) = (2 + x)^2 \quad \text{and} \quad v(x) = x^2 + 2
\]
First, find \( u'(x) \) and \( v'(x) \):
1. **Differentiate \( u(x) = (2 + x)^2 \) using the **Chain Rule**:
\[
u'(x) = 2(2 + x) \cdot \frac{d}{dx}(2 + x) = 2(2 + x) \cdot 1 = 2(2 + x)
\]
2. **Differentiate \( v(x) = x^2 + 2 \):**
\[
v'(x) = 2x
\]
Apply the Product Rule:
\[
f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x) = 2(2 + x)(x^2 + 2) + (2 + x)^2 \cdot 2x
\]
Factor out \( 2(2 + x) \):
\[
f'(x) = 2(2 + x)\left[ x^2 + 2 + x(2 + x) \right]
\]
\[
= 2(2 + x)\left[ x^2 + 2 + 2x + x^2 \right]
\]
\[
= 2(2 + x)(2x^2 + 2x + 2)
\]
We can factor out a 2 from the quadratic polynomial:
\[
= 2(2 + x) \cdot 2(x^2 + x + 1) = 4(2 + x)(x^2 + x + 1)
\]
**Final Answer:**
\[
f'(x) = 4(x + 2)(x^2 + x + 1)
\]
---
**Summary of Derivatives:**
1. **(a)** \( \displaystyle f'(x) = (3x + 2)(9x + 2) \)
2. **(b)** \( \displaystyle f'(x) = (x - 3)(3x - 1) \)
3. **(c)** \( \displaystyle f'(x) = (4x + 1)^3 (29 - 60x) \)
4. **(d)** \( \displaystyle f'(x) = 4(x + 2)(x^2 + x + 1) \)
If you have any further questions or need additional clarification on any of the steps, feel free to ask!
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution